GENERATIVE DESIGN IN ARCHITECTURE: ARTIFICIAL INTELLIGENCE AND THE FUTURE OF ARCHITECTURAL SOLUTIONS - A. R. Abobakirov (Modern American Journals, 2025)
contemporary architectural paradigm, reshaping how architects conceive, develop, and optimize spatial solutions by embedding artificial intelligence (AI) into the core of design workflows. Unlike traditional computer-aided design (CAD) and even parametric approaches, generative design is not merely a tool for representing ideas but a collaborative process where AI algorithms autonomously generate and evaluate thousands of design alternatives in response to user-defined goals and constraints. Powered by evolutionary algorithms, machine learning, genetic optimization, and generative adversarial networks (GANs), this approach allows architects to explore multidimensional solution spaces where structural performance, environmental efficiency, spatial organization, and aesthetic expression can be simultaneously balanced. The integration of AI platforms such as Autodesk Generative Design, Spacemaker AI, and the coupling of Grasshopper with neural networks demonstrates how computation transcends representation to become an intelligent design partner. Case studies from global practices illustrate AI-generated office buildings, residential districts optimized for daylight and wind flow, and adaptive urban planning schemes that exemplify the potential of this methodology. The results confirm that generative design enables architectural innovation by dramatically accelerating iteration cycles, discovering non-intuitive solutions, and embedding sustainability as a computational parameter rather than an afterthought. However, critical discussion reveals challenges including the opacity of algorithmic decision-making, ethical implications of AI-driven design, the displacement of human creativity, and technological dependency. In the Uzbek context, generative design opens opportunities to reinterpret traditional forms such as domes, muqarnas, and ornamental patterns by integrating them into AI-driven optimization frameworks, creating hybrid solutions that respect cultural heritage while embracing computational intelligence. This article concludes that generative design represents not merely an evolution of digital architecture but a new epistemology of design, where artificial intelligence transforms architecture into a dialogue between human intention, algorithmic exploration, and material realization.
Keywords: Generative Design; Artificial Intelligence; Evolutionary Algorithms; Machine Learning; Architecture; Computational Design; Optimization; Autodesk Generative Design; Spacemaker AI; Uzbekistan